THE CONTRIBUTION OF ṢAFIYYAH BINT ḤUYAYY IN HADITH TRANSMISSION IN AL-KUTŪB AL-TIS’AH - Al-Qosam, Muhammad 'Izzuddin; Anam, Khoirul; ., Hartati; ., Umayah (Jurnal Studi Hadis Nusantara, 2025)
In the narration of hadith, there is a significant disparity between men and women, with male narrators being far more dominant than female narrators. This research aims to examine the narrations of Ṣafiyyah binti Ḥuyay, the wife of the Prophet Muhammad SAW, in al-Kutūb al-Tis’ah using a literature-based qualitative methodology. Although Ṣafiyyah lived with the Prophet for only about three or four years, she managed to collect and narrate twenty-four hadiths from him, along with several other narrations outside of the nine books. Ṣafiyyah conveyed these hadiths to five of her students: ‘Alī bin al-Ḥusain, Muslim bin Ṣafwān, Ṣuhairah binti Jaifir, Kinānah, and Syumaisah. These hadiths have been transmitted by various narrators with varying levels of credibility, including both powerful and weak narrators, resulting in some hadiths being classified as ṣaḥīḥ (authentic) and others as ḍa’īf (weak). The substance of the narrated hadiths covers themes such as the I’tikaf of the Prophet Muhammad SAW at the end of Ramadan, the fermentation of grapes, the attack on the Ka’bah in the end times, the Prophet’s defence of Ṣafiyyah, teachings on remembrance (dhikr), and the pilgrimage journey of the Prophet with his companions. In the ever-evolving modern era, the role of women in science is crucial for the advancement of society. Without individuals studying hadith, future generations will not be aware of the life of the Prophet Muhammad SAW.